2007
DOI: 10.1128/aem.00419-07
|View full text |Cite
|
Sign up to set email alerts
|

Pathotyping Escherichia coli by Using Miniaturized DNA Microarrays

Abstract: The detection of virulence determinants harbored by pathogenic Escherichia coli is important for establishing the pathotype responsible for infection. A sensitive and specific miniaturized virulence microarray containing 60 oligonucleotide probes was developed. It detected six E. coli pathotypes and will be suitable in the future for high-throughput use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 25 publications
2
58
0
Order By: Relevance
“…We also compared isolates originating from septicemia and found that this isolate did not appear to be different from others in terms of serogroups, resistance profi le, and virulence factor. In the present study, all strains were OXA-I-derived ESBLs which appears to be important for ceftazidime hydrolysis as reported earlier [19]. Their presence seems to infl uence the level of resistance to penicillins conferred to isolates.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…We also compared isolates originating from septicemia and found that this isolate did not appear to be different from others in terms of serogroups, resistance profi le, and virulence factor. In the present study, all strains were OXA-I-derived ESBLs which appears to be important for ceftazidime hydrolysis as reported earlier [19]. Their presence seems to infl uence the level of resistance to penicillins conferred to isolates.…”
Section: Discussionsupporting
confidence: 51%
“…A miniaturized E. coli oligonucleotide virulence array that had previously been designed was used for this work [19]. Eighteen genes were specifi c to a particular E. coli patho type, 13 were common between two more pathotypes, and seven were unassigned.…”
Section: Microarraymentioning
confidence: 99%
See 1 more Smart Citation
“…It could be used in search for virulence genes [39] as well as resistance genes [40,41]. Although 99% correlation between PCR and microarray approaches was provided [40], the latter seems to be less common in the literature concerning ARGs.…”
Section: Args Occurring In Arb and Dna Isolated From Tap Watera Reviewmentioning
confidence: 99%
“…A serotype-specific DNA microarray for the identification of clinically encountered Shigella and pathogenic E. coli strains has being described . Diagnostic microarrays based on the ArrayTube format were devised for virulence determinant detection as well as for protein-based serotyping of E. coli (Korczak et al, 2005;Anjum et al, 2007). A novel ArrayTube assay, which incorporates oligonucleotide DNA probes representing 24 of the most epidemiologically relevant O antigens and 47 H antigens, has been described for fast DNA serotyping of E. coli .…”
Section: Comparative Genomics and Microbial Typingmentioning
confidence: 99%